Plant parasitic nematodes in subtropical and tropical agriculture (CABI Publishing, 2005)
This book covers all aspects of plant nematology in subtropical and tropical agriculture. It covers nematode pests of all the major food and cash crops including; rice, cereals, root and tubers, potato, food legumes, vegetables, peanut, citrus, tree and fruit crops, coconut and other palms, cocoa, tea, bananas, sugarcane, tobacco, pineapple, cotton, other tropical fibers, spices, condiments and medicinal plants. It also provides practical guidance on methods of extraction, processing and diagnosing of different plant and soil nematodes.